Humidity-sensitive chemoelectric flexible sensors based on metal-air redox reaction for health management - Li, Shuo; Zhang, Yong; Liang, Xiaoping; Wang, Haomin; Lu, Haojie; Zhu, Mengjia; Wang, Huimin; Zhang, Mingchao; Qiu, Xinping; Song, Yafeng; Zhang, Yingying (Nature communications, 2022)
Numerous studies have shown flexible electronics play important roles in health management. The way of power supply is always an essential factor of devices and self-powered ones are very attractive because of the fabrication easiness, usage comfort and aesthetics of the system. In this work, based on the metal-air redox reaction, which is usually used in designing metal-air batteries, we design a self-powered chemoelectric humidity sensor where a silk fibroin (SF) and LiBr gel matrix containing parallel aligned graphene oxide (GO) flakes serve as the electrolyte. The abundant hydrophilic groups in GO/SF and the hygroscopicity of LiBr lead to tight dependence of the output current on the humidity, enabling the sensor high sensitivity (0.09 μA/s/1%), fast response (1.05 s) and quick recovery (0.80 s). As proofs of concept, we design an all-in-one respiratory monitoring-diagnosing-treatment system and a non-contact human-machine interface, demonstrating the applications of the chemoelectric humidity sensor in health management. Self-powered sensors are of interest in wearable technology and other applications. Here, the authors report on the creation of a metal-air redox reaction humidity sensor where the conductance and charge generated is influenced by the amount of absorbed water and demonstrate application in respiration monitoring.